Fecal microbiota transplantation in patients with slow-transit constipation: A randomized, clinical trial. - Hongliang Tian (PLoS ONE, 2017)
Fecal microbiota transplantation has been proposed as a therapeutic approach for chronic constipation. This randomized, controlled trial aimed to compare the effects of conventional treatment alone (control) with additional treatment with FMT (intervention) in patients with slow-transit constipation (STC). Adults with STC were randomized to receive intervention or control treatment. The control group received education, behavioral strategies, and oral laxatives. The intervention group was additionally provided 6 days of FMT. The primary endpoint was the clinical cure rate (proportion of patients achieving a mean of ≥ three complete spontaneous bowel movements [CSBMs] per week]. Secondary outcomes and safety parameters were assessed throughout the study. Sixty patients were randomized to either conventional treatment alone (n = 30) or FMT (n = 30) through a nasointestinal tube. There were significant differences between the intervention group and control group in the clinical improvement rate (intention-to-treat [ITT]: 53.3% vs. 20.0%, P = 0.009), clinical cure rate (ITT: 36.7% vs. 13.3%, P = 0.04), mean number of CSBMs per week (ITT: 3.2 ± 1.4 vs. 2.1 ± 1.2, P = 0.001), and the Wexner constipation score (ITT: 8.6 ± 1.5 vs. 12.7 ± 2.5, P < 0.00001). Compared with the control group, the intervention group showed better results in the stool consistency score (ITT: 3.9 vs. 2.4, P < 0.00001) and colonic transit time (ITT: 58.5 vs. 73.6 h, P < 0.00001). The intervention group had more treatment-related adverse events than did the control group (50 vs. 4 cases). FMT was significantly more effective (30% higher cure rate) for treatment of STC than conventional treatment. No serious adverse events were observed.